Experimental Study on Soaked Corn Cobs as Feedstock for Biomass Gasification in an Open Downdraft Gasifier - Kosim, Muhtar; Kasda, Kasda; Saputra, Dede Iman; Kurnia, Yuda; Setioputro, Novandri Tri (Green Engineering Society, 2025)
Fossil fuels, which account for 83% of Indonesia's total energy supply, are depleting and environmentally unsustainable. Corn cob biomass, with an annual yield of 4.34 million metric tons, presents a viable alternative. Through gasification at temperatures of 700–1200°C, corn cobs can be converted into combustible gas or syngas. To enhance syngas yield, the corn cob gasification process can be optimized by increasing moisture content through soaking. However, experiments with soaked corn cobs have shown a significant decline in temperature and gasification zone performance. The gasification temperature decreased from 1024°C to 614°C, falling below the 700°C threshold. Additionally, the gasification zone shifted significantly downward in the reactor. This reduction is attributed to the high moisture content of the corn cobs, which exceeded 30%, reaching 56.78%, allowing the gasification process to last for 48 minutes. Before the gasifier ceased operation, syngas production achieved a promising average thermal power of 1.76 kW with an efficiency of 7.14%. These findings indicate that soaked corn cobs can serve as biomass gasification feedstock, provided the moisture content does not exceed 30%.